Performance-Based Structural Fire Engineering of Steel Building Structures: Traveling Fires - Fischer, Erica C.; Varma, Amit H.; Gordon, James A. (Frontiers in Built Environment, 2022)
Many studies and observations of large building fires show that in large compartments, fires do not burn uniformly. Rather, fires will burn locally and move across a floor plate as fuel is con-sumed. Currently fire engineering practice assumes uniformly burning fires within a compart-ment and the fire design methodologies are based upon small compartment fire scenarios. Trav-eling fire modeling that accounts for fire dynamics is essential for performance-based fire engi-neering. This paper reviews two traveling fire models presented in literature and implements both models on a steel-frame building. An advanced analysis of the building is performed and the fire performance of the building in these travel fire scenarios are compared to the fire perfor-mance of the building when subjected to conventional fire exposure scenarios (full story fires or compartment fires). The authors then illustrate the use of structural fire engineering methodolo-gies to improve the fire resistance of the building.